2012
DOI: 10.1016/j.devcel.2012.08.005
|View full text |Cite|
|
Sign up to set email alerts
|

The Sphingosine-1-Phosphate Receptor S1PR1 Restricts Sprouting Angiogenesis by Regulating the Interplay between VE-Cadherin and VEGFR2

Abstract: Angiogenesis, the process by which new blood vessels arise from preexisting ones, is critical for embryonic development and is an integral part of many disease processes. Recent studies have provided detailed information on how angiogenic sprouts initiate, elongate, and branch, but less is known about how these processes cease. Here, we show that S1PR1, a receptor for the blood-borne bioactive lipid sphingosine-1-phosphate (S1P), is critical for inhibition of angiogenesis and acquisition of vascular stability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
233
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(261 citation statements)
references
References 42 publications
(51 reference statements)
15
233
1
1
Order By: Relevance
“…26,27 Similar embryo lethality around E12.5 was found in S1pr1 or Klf2 knockout mice as a result of severe bleeding throughout the bodies because of defect in maturation of blood vessels, 34,35 suggesting that they both are important in vasculature formation. Klf2 was reported to be a crucial transcription factor to enhance S1pr1 expression in T cells.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…26,27 Similar embryo lethality around E12.5 was found in S1pr1 or Klf2 knockout mice as a result of severe bleeding throughout the bodies because of defect in maturation of blood vessels, 34,35 suggesting that they both are important in vasculature formation. Klf2 was reported to be a crucial transcription factor to enhance S1pr1 expression in T cells.…”
Section: Discussionmentioning
confidence: 82%
“…It has been shown that S1P/S1pr1 signaling restricted angiogenic sprouting and stabilized junctional VE-cadherin, which played an important role in the maintenance of vascular integrity and the regulation of vascular permeability. 27 Here, we showed that elevation of miR302-367 expression in ECs upregulated S1pr1, leading to the increased VE-cadherin at endothelial junctions, which restricted retina angiogenesis and improved vascular stability. Either pharmacological or genetic deletion of S1pr1 reversed the upregulation of total and junctional VEcadherin, hence boosted retina angiogenesis and weakened the vascular stability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism by which ceramide regulates transcription factor HIF-1a requires more investigation. Sphingosine-1-phosphate (S1P), which is a counterpart of ceramide in cell death and proliferation, is well known as a stimulant of angiogenesis [37]. After treatment with dietary Glu-Cer, the serum levels of S1P did not change significantly (data not shown), suggesting that serum S1P may not play a role in angiogenesis in this xenograft model.…”
Section: Discussionmentioning
confidence: 83%